Can in Shakespeare and Marlowe - Skorasińska, Monika (Studia Anglica Posnaniensia, 2014)
This paper seeks to present the main meanings and the use of the modal verb can in the plays of two Early Modern English playwrights, William Shakespeare and Christopher Marlowe. In particular, the study aims at presenting a comparative analysis and provides descriptive as well as quantitative data. The research is based on the analysis of the corpus consisting of the plays written by Shakespeare and Marlowe between 1593-1599. The choice of the works is not random but includes the plays which bear the strongest resemblance in terms of theme, structure, and most importantly, the language of both authors.